Steady‐State Pre‐rRNA Analysis to Investigate the Functional Microbiome. Issue 7 (27th July 2021) - Weigel, Kris M.; Olson, Alaina M.; Cangelosi, Gerard A.
Abstract: The gut microbiome is recognized as a critical regulator of human diseases. Constituents of the microbiota and their individual activities can affect a broad range of disease states related to autoimmunity, cancer, infection, metabolism, mental health, and toxicant exposure. A substantial number of microbiome species are not culturable, limiting their study in vitro. Sequencing methods have allowed quantification of the composition of the microbiome, but methods to characterize the physiological status of bacterial species remain limited. Ribosomal RNA precursors (pre‐rRNAs) are species‐specific intermediates in bacterial ribosomal synthesis, and their levels are highly responsive to environmental changes. Immediately before and during active growth, pre‐rRNA levels are high, whereas in non‐dividing cells, copy numbers are orders of magnitude lower. These dynamics are conserved in all bacterial species and occur exclusively in viable cells, allowing the specific characterization of living and functional bacteria in their native states. Pre‐rRNA analysis has been shown to yield valuable real‐time information on the physiology of individual bacterial species within complex samples, beyond what traditional qPCR and sequencing methods can offer. Herein, we describe a PCR‐based protocol to interrogate and quantify the in situ growth status of bacterial species of interest within a complex microbiome. We also describe an in vitro protocol to characterize the pre‐rRNA/growth relationship for a given bacterial species to provide greater context for values obtained from natural samples. Improved understanding of microbial physiological responses to exposures could reveal novel toxicological mechanisms, biomarkers, and potential treatments. © 2021 Wiley Periodicals LLC. Basic Protocol : Targeted steady‐state pre‐rRNA analysis Support Protocol : Characterization of pre‐rRNA/growth relationship